2005
DOI: 10.1103/physrevlett.94.155701
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Opalescence at theαβTransition of Quartz: Role of the Incommensurate Phase Studied by Synchrotron Radiation

Abstract: The origin of the light scattering observed at the alpha-beta transition of quartz is still a subject of controversy. We present structural studies performed during the coexistence of the alpha and the intermediate incommensurate (inc) phases using simultaneously synchrotron x-ray diffraction and optical techniques. The small and large angle light scatterings are due, respectively, to the orientation domains of the 3q inc phase and to the alpha phase twins revealed by diffuse x-ray scattering. In the vicinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(46 reference statements)
2
5
1
Order By: Relevance
“…Based on the synchrotron radiation and neutron diffraction observations by Dolino et al, 1,2 in the following we show that ͑i͒ The observed long-period IC modulation in quartz is a pure transversal acoustic ͑TA͒ modulation, without longitudinal acoustic ͑LA͒ and optic mode components. ͑ii͒ A long-period acoustic modulation cannot appear spontaneously as a result of the IC phase transition associated with the acoustic mode softening, and the mechanism of its formation should be understood.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Based on the synchrotron radiation and neutron diffraction observations by Dolino et al, 1,2 in the following we show that ͑i͒ The observed long-period IC modulation in quartz is a pure transversal acoustic ͑TA͒ modulation, without longitudinal acoustic ͑LA͒ and optic mode components. ͑ii͒ A long-period acoustic modulation cannot appear spontaneously as a result of the IC phase transition associated with the acoustic mode softening, and the mechanism of its formation should be understood.…”
supporting
confidence: 52%
“…͑ii͒ A long-period acoustic modulation cannot appear spontaneously as a result of the IC phase transition associated with the acoustic mode softening, and the mechanism of its formation should be understood. ͑iii͒ Such a modulation cannot be at the origin of any observed light scattering anomalies, contrary to the interpretation by Dolino et al 1 IC satellite reflections, in general, are contributed by the atomic displacements with respect to the crystal lattice cell ͑optical displacements͒, and by the acoustic displacements, i.e., by the displacements of a lattice cell as a whole. ͑Such a presentation should be viewed only as a simplified geometrical illustration, since the acoustic-optic mode coupling induces distortions of the lattice cells.͒ In the case of the IC structure of quartz, as shown in the present paper, one can distinguish these two contributions for some satellites, and define some important features of the IC structure.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Spectroscopic techniques such as the Raman scattering [29,31,32], infrared [30], light scattering [11,27] X-ray and neutron diffraction [9,10,22,33,36,37] have been used to investigate the a and b structures in quartz.…”
Section: Introductionmentioning
confidence: 99%
“…In situ transmission electron microscopy (TEM) showed that the phase transition is accompanied by submicroscopic Dauphiné twinning (Van Tendeloo et al 1976;Heaney and Veblen 1991a) and an incommensurate structure has been identified (Bastie et al 1988;Dolino et al 2005). Host and twin are geometrically related by a 180°rotation around the c-axis.…”
Section: Introductionmentioning
confidence: 99%